If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + -8) = -4(4x + -1) Reorder the terms: -3(-8 + 2x) = -4(4x + -1) (-8 * -3 + 2x * -3) = -4(4x + -1) (24 + -6x) = -4(4x + -1) Reorder the terms: 24 + -6x = -4(-1 + 4x) 24 + -6x = (-1 * -4 + 4x * -4) 24 + -6x = (4 + -16x) Solving 24 + -6x = 4 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 24 + -6x + 16x = 4 + -16x + 16x Combine like terms: -6x + 16x = 10x 24 + 10x = 4 + -16x + 16x Combine like terms: -16x + 16x = 0 24 + 10x = 4 + 0 24 + 10x = 4 Add '-24' to each side of the equation. 24 + -24 + 10x = 4 + -24 Combine like terms: 24 + -24 = 0 0 + 10x = 4 + -24 10x = 4 + -24 Combine like terms: 4 + -24 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| 4+5x=4x+13 | | 2x+y=3-8 | | X+25+26+27=78 | | 3/2x9/2x-18 | | 100=8d | | -12-5(6-2m)=8 | | 87=4z+27 | | 11p-33=5p+5 | | 7-5y+2-1= | | 3+9+3x-1+5x+9x=96 | | x/5-15=x/4 | | -(5x-6)=4-7x | | 5.5=82.5k | | X+2+2=70 | | 5.5=82.5 | | 21t^2-18t+3=0 | | 21t^2-18t-3=0 | | 15m=56 | | 3(2x-5)=2(3x+1) | | -5x^2-60-20=0 | | (5x-6)^1/2=x | | -4.9t^2+8t+63=0 | | X+2+2=18 | | 1/x=0.88 | | 35q=70 | | 4.3x+7-7.3x=10 | | 2.8+0.5x=0.3 | | T+.2=5 | | -0.6x+7.38=-0.4x+1.38 | | 4m(-3)m+2=12 | | 500=d | | 7x-31+5x+13=180 |